2011
DOI: 10.3389/fnint.2010.00129
|View full text |Cite
|
Sign up to set email alerts
|

Altered Auditory and Multisensory Temporal Processing in Autism Spectrum Disorders

Abstract: Autism spectrum disorders (ASD) are characterized by deficits in social reciprocity and communication, as well as by repetitive behaviors and restricted interests. Unusual responses to sensory input and disruptions in the processing of both unisensory and multisensory stimuli also have been reported frequently. However, the specific aspects of sensory processing that are disrupted in ASD have yet to be fully elucidated. Recent published work has shown that children with ASD can integrate low-level audiovisual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
256
6
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 271 publications
(277 citation statements)
references
References 52 publications
14
256
6
1
Order By: Relevance
“…Various researchers have determined that there does exist an extended temporal binding window in ASD, meaning that individuals with ASD continue to integrate sensory information over a larger gap in time than do TD individuals (Foss-Feig et al 2010;Kwakye et al 2011;Woynaroski et al 2013). The current results indicating that the ASD group had significantly lower accuracy than the TD group on the 2F1B (i.e., fusion illusion) and 2F0B trials may be explained by the presence of an expanded temporal binding window.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Various researchers have determined that there does exist an extended temporal binding window in ASD, meaning that individuals with ASD continue to integrate sensory information over a larger gap in time than do TD individuals (Foss-Feig et al 2010;Kwakye et al 2011;Woynaroski et al 2013). The current results indicating that the ASD group had significantly lower accuracy than the TD group on the 2F1B (i.e., fusion illusion) and 2F0B trials may be explained by the presence of an expanded temporal binding window.…”
Section: Discussionmentioning
confidence: 48%
“…Temporal binding windows allow multisensory information to be integrated even when there might be slight temporal asynchronies . In individuals with ASD, it appears that there might be an enlarged or expanded temporal binding window as compared to TD individuals (Baum et al 2015;Foss-Feig et al 2010;Kwakye et al 2011;Stevenson et al 2014a;Wallace and Stevenson 2014). This would mean that individuals with ASD would perceive asynchronous stimuli as simultaneous more so than TD individuals would.…”
mentioning
confidence: 99%
“…Previous studies on time perception in ASD using a variety of auditory paradigms such as duration discrimination of complex tones (e.g., Lepistö et al, 2006), temporal processing of complex low-level auditory information (Alcántara, Weisblatt, Moore and Bolton, 2004;Alcántara, Cope, Cope and Weisblatt, 2012;Groen et al, 2009) and temporal order judgment tasks (Kwakye, Foss-Feig, Cascio, Stone and Wallace, 2011) have provided evidence for diminished abilities in auditory temporal processing. It is also found that children with ASD have difficulties reproducing the lengths of auditory stimuli of standardized durations (Szelag, Kowalska, Galkowski and Pöppel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant is also the increased prevalence of absolute pitch and musical savants in the ASD population (e.g., DePape et al 2012;Heaton et al 2008a, b, c;Miller 1989;Mottron et al 2013) and the increased prevalence of autistic traits among possessors of absolute pitch (e.g., Dohn et al 2012). The occurrence of this superior pitch processing contrasts with the inferior temporal processing abilities in ASD (such as impaired gap-in-noise detection, duration discrimination, temporalenvelope processing, temporal order judgement; e.g., Alcántara et al 2012;Bhatara et al 2013;Kwakye et al 2011;Lepisto et al 2005Lepisto et al , 2006Samson et al 2011; but see Jones et al 2009;Kasai et al 2005) and the evidence of speech perception impairments (Alcántara et al 2004;Bhatara et al 2013;Groen et al 2009) and generally delayed speech and language development (e.g., Anderson et al 2007). Speech perception has been shown to be particularly impaired while presented in noise with temporal dips (Alcántara et al 2004;Groen et al 2009) or in a competing talker condition (Alcántara et al 2004;Bhatara et al 2013).…”
Section: Introductionmentioning
confidence: 99%